Authentication of Lemongrass Oil By Gas Chromatography-Mass Spectroscopy (GC-MS) Combination Chemometrics - Any Guntarti; Husnun Khairunnisa Pratiwi; Laela Hayu Nurani; Ibnu Gholib Gandjar (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
The addition of something foreign to lemongrass essential oil has been done since ancient times. One way is to add turpentine oil which aims to increase the volume and grade of the smell. The purpose of this study was to determine the authentication of citronella oil using the gas chromatography-mass spectrometry (GC-MS) method combined with multivariate PCA analysis. Fragrant lemongrass oil was isolated by distillation of water and using simplicia in the form of powdered dried Cymbpogon citratus leaves. The oil obtained was treated with anhydrous Na2SO4. The results of the characteristics and quality requirements of citronella oil are compared with the SNI. The results of GC-MS analysis were the relative levels of essential oils. The results of the characteristic test meet the quality requirements of SNI 06-3953-1995, except for the yield requirements. The results of analysis by GC-MS, the essential content of citronella oil was citronella (37.47%), geraniol (25.03%), trans-caryophilene (3.69%), citronellol (11.68%), and delta cadinene. (2.44%). Chemometric principle component analysis (PCA) can group samples of fragrant lemongrass oil, turpentine oil and lemongrass oil products on the market.